Circular cylinder wakes and vortex-induced vibrations - Bearman, P.W. (Journal of fluids and structures, 2011)
This paper presents a selective review of recent research on vortex-induced vibrations of isolated circular cylinders and the flow and vibration of circular cylinders in a tandem arrangement; a common thread being that the topics raised are of particular interest to the author. The influence of Reynolds number on the response of isolated cylinders is presented and recent developments using forced vibration are discussed. The response of a cylinder free to respond in the in-line and transverse directions is contrasted with that of a cylinder responding in only one direction. The interference between two circular cylinders is discussed and prominence given to the case of cylinders in a tandem arrangement. The origin of the time–mean lift force on the downstream cylinder is considered together with the cause of the large amplitude transverse vibration experienced by the cylinder above vortex resonance. This wake-induced vibration is shown to be a form of vortex-induced vibration.